(untitled) (Journal of Civil Engineering Researchers, 2024)
Effective waste management is crucial for urban sustainability and environmental conservation. This study evaluates the efficiency and quality of compost produced through normal and thermophilic in-vessel composting and anaerobic digestion within a neighborhood waste management model. By analyzing physicochemical properties, process temperatures, carbon to nitrogen ratios, germination index, and biogas production rates, the study highlights the advantages of integrating these methods. Results indicate that thermophilic in-vessel composting accelerates the composting process, achieving rapid temperature increases and enhanced microbial activity. Anaerobic digestion complements this by producing biogas and yielding high-quality compost with low phytotoxicity. The combined approach not only optimizes compost production and quality but also contributes to renewable energy generation and reduced greenhouse gas emissions. These findings provide a framework for implementing sustainable, localized waste management systems, offering significant insights for policy and operational decisions in municipal waste management.